Severe Vitamin D Deficiency May be an Additional Cofactor for the Occurrence of Alcoholic Steatohepatitis. (2nd May 2015) - Anty, Rodolphe; Canivet, Clémence M.; Patouraux, Stéphanie; Ferrari‐Panaia, Patricia; Saint‐Paul, Marie Christine; Huet, Pierre‐Michel; Lebeaupin, Cynthia; Iannelli, Antonio; Gual, Philippe; Tran, Albert
<x xml:space="preserve">Abstract</x> Background Among its pleiotropic effects, vitamin D may protect the liver from fibrosis and/or inflammation. However, the impact of vitamin D on liver pathology in hepatitis C remains unclear, and very few studies including alcoholic patients with liver pathologies have been performed. Here we compared the levels of 25‐OH vitamin D in the blood of alcoholic patients with the occurrence of alcoholic steatohepatitis (ASH) or bridging fibrosis. Methods One hundred and one alcoholic patients were included. All the patients received a liver biopsy, and the levels of 25‐OH vitamin D were evaluated with the Liaison 25‐OH vitamin D assay. Logistic regression analyses were performed to obtain predictive factors of liver histology. Results Among alcoholic patients, 40.6% presented ASH and 39.6% presented bridging fibrosis. A severe deficiency in 25‐OH vitamin D (<10 ng/ml) was seen in 60.4% of patients. This deficiency was frequent in patients with ASH (85.4%) and in those with bridging fibrosis (80%) but was independently associated only with ASH (odds ratio = 8.46 [95% confidence interval 2.05 to 34.89], p = 0.003). Conclusions In alcoholic patients, a severe deficiency in 25‐OH vitamin D was independently associated with the occurrence of ASH.